Integrative Taxonomy of Amazon Reefs' Arenosclera spp.: A New Clade in the Haplosclerida (Demospongiae) - Leal, Camille V.; Moraes, Fernando C.; Fróes, Adriana M.; Soares, Ana C.; de Oliveira, Louisi S.; Moreira, Ana Paula B.; Thompson, Fabiano L.; Hajdu, Eduardo (Frontiers in Marine Science, 2017)
Two new Arenosclera are described here on the basis of materials obtained from Amazon reefs in 2014, A. amazonensis sp. nov. and A. klausi sp. nov. Both are clearly distinct from all other Arenosclera by their erect, solid funnel to lamellate habit, larger oxeas, and ectosomal architecture bearing occasional multispicular tracts. An integrative approach to find the best classification for both new species failed to group them and A. heroni, the genus’ type species. Nearly complete 28S rRNA sequences obtained from these species’ metagenomes suggested instead a better placement for the new species and A. brasiliensis in clade C (sensu Redmond et al., 2013), while A. heroni fits best in clade A. We propose to name three clades according to the rules of the PhyloCode: Arenospiculap, Dactyclonap and Dactyspiculap, respectively for the clade originating with the most recent common ancestor of the three Brazilian Arenosclera spp.; the most inclusive clade containing Dactylia varia (Gray, 1843) and Haliclona curacaoensis (van Soest, 1980); and the least inclusive clade containing Arenospiculap and Dactyclonap. A Karlin dinucleotide dissimilarity analysis of metagenomes carried out on cryopreserved samples recognized A. amazonensis sp. nov. as the most dissimilar species, thus suggesting a more particular microbiota is present in this Amazon species, an open avenue for extended applied study of this holobiont.